Evaluation in Context - Thompson, Geoff, 1960-; Alba-Juez, Laura (Pragmatics & beyond, 2014)
This chapter explores evaluative discourse on social networking sites (henceforth SNSs), paying special attention to the role played by the expression of attitude and positive politeness in the management of interpersonal rapport. The corpus for the study consists of a random sample of 100 messages exchanged among university students in the United Kingdom and the United States on a particular site, i.e., Facebook, during the two-year period 2010-2012. Analysis is approached from the theories of appraisal (Martin and White 2005; Bednarek 2008) and politeness (Brown and Levinson 1987); and the m.